Impact of serum 1,5-anhydro-d-glucitol level on the prediction of severe coronary artery calcification: an intravascular ultrasound study - Wada, Hideki (Cardiovasc Diabetol, 2019)
BACKGROUND: A low 1,5-anhydro-d-glucitol (AG) blood level is considered a clinical marker of postprandial hyperglycemia. Previous studies reported that 1,5-AG levels were associated with vascular endothelial dysfunction and coronary artery disease (CAD). However, the association between 1,5-AG levels and coronary artery plaque in patients with CAD is unclear. METHODS: This study included 161 patients who underwent percutaneous coronary intervention for CAD. The culprit plaque characteristics and the extent of coronary calcification, which was measured by the angle of its arc, were assessed by preintervention intravascular ultrasound (IVUS). Patients with chronic kidney disease or glycosylated hemoglobin ≥ 7.0 were excluded. Patients were divided into 2 groups according to serum 1,5-AG levels (< 14.0 μg/mL vs. ≥ 14 μg/mL). RESULTS: The total atheroma volume and the presence of IVUS-attenuated plaque in the culprit lesions were similar between groups. Calcified plaques were frequently observed in the low 1,5-AG group (p = 0.06). Compared with the high 1,5-AG group, the low 1,5-AG group had significantly higher median maximum calcification (144° vs. 107°, p = 0.03) and more frequent calcified plaques with a maximum calcification angle of ≥ 180° (34.0% vs. 13.2%, p = 0.003). Multivariate logistic regression analysis showed that a low 1,5-AG level was a significant predictor of a greater calcification angle (> 180°) (OR 2.64, 95% CI 1.10–6.29, p = 0.03). CONCLUSIONS: Low 1,5-AG level, which indicated postprandial hyperglycemia, was associated with the severity of coronary artery calcification. Further studies are needed to clarify the effects of postprandial hyperglycemia on coronary artery calcification.